(untitled) (Dimensión Antropológica, 2022)
This work analize the role of stonemasons or stone workers, their activities and the way in which they were organized to carry out the stone estraction work. He also focuses his attention on the techniques used from the analysis of tols and knowledge of landscapes. Little-know pictorial documents and manuscripts were use for the study.